2012
DOI: 10.1093/nar/gks1013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions suggest multiple distinct roles of the arch and core helicase domains of Mtr4 in Rrp6 and exosome function

Abstract: The RNA exosome is responsible for a wide variety of RNA processing and degradation reactions. The activity and specificity of the RNA exosome is thought to be controlled by a number of cofactors. Mtr4 is an essential RNA-dependent adenosine triphosphatase that is required for all of the nuclear functions of the RNA exosome. The crystal structure of Mtr4 uncovered a domain that is conserved in the RNA exosome cofactors Mtr4 and Ski2 but not in other helicases, suggesting it has an important role related to exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…They were also less recovered with Mtr4Δarch relative to Mtr4, consistent with pre-rRNA maturation defects reported for strains carrying arch mutations (Fig. S1C) 13, 14, 38, 39 . In contrast, the major ncRNA classes, CUTs, SUTs and XUTs, were strongly recovered with Air2 and Trf4, relative to Air1 plus Trf5.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…They were also less recovered with Mtr4Δarch relative to Mtr4, consistent with pre-rRNA maturation defects reported for strains carrying arch mutations (Fig. S1C) 13, 14, 38, 39 . In contrast, the major ncRNA classes, CUTs, SUTs and XUTs, were strongly recovered with Air2 and Trf4, relative to Air1 plus Trf5.…”
Section: Resultssupporting
confidence: 88%
“…We compared strains in which the endogenous gene was HTP tagged for Air1, Air2, Trf4, Trf5, and Mtr4, as well as the exosome exonucleases Rrp44 and Rrp6. The Mtr4 arch domain is implicated in substrate recruitment 13, 14, 38, 39 , so we also constructed and analyzed a tagged Mtr4 mutant lacking this region (Mtr4Δarch) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, depletion of Mtr4 or deletion of the arch domain induced accumulation of several rRNA substrates, which included not only 5.8S rRNA precursors but also the 5 0 ETS fragment (cleaved from the 35S rRNA precursor during rRNA processing), which was no longer degraded by the exosome (de la Cruz et al, 1998;Jackson et al, 2010;Klauer and van Hoof, 2013). When the N terminus of Nop53, required for interaction with Mtr4, was truncated ( Figure 1D), an accumulation of 5.8S precursors (7S and 5.8S+30) was observed, whereas the 5 0 ETS remained unaffected ( Figure 1F).…”
Section: Nop53 Interacts Directly With the Exosome-associated Helicasmentioning
confidence: 99%
“…This domain emanates from the helicase core and is composed of two anti-parallel coiled coils, followed by the globular b-barrel structure, termed the KOW (Kyrpides-Ouzounis-Woese), a domain that is found in a number of ribosomal proteins. In vivo analysis has linked the Mtr4 arch domain to a subset of exosome-mediated processes that include the maturation of the 5.8S rRNA and degradation of the 5 0 ETS (external transcribed spacer) rRNA spacer fragment (Klauer and van Hoof, 2013). Additionally, it has been suggested that the arch is involved in RNA binding, since the KOW domain of Mtr4 and the equivalent domain in Ski2 can bind RNA in vitro (Halbach et al, 2012;Weir et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The helicase regions contain the DExH core typical of processive 3 ′ -5 ′ RNA-dependent ATPases as well as a specialized insertion generally known as the "arch" domain for its characteristic curved structure (Jackson et al 2010;Weir et al 2010;Halbach et al 2012;Johnson and Jackson 2013). In vivo, the arch of Mtr4 is required for 5.8S rRNA maturation and 5 ′ ETS degradation (Jackson et al 2010;Klauer and van Hoof 2012) while the arch of Ski2 promotes the cytoplasmic functions of the exosome (Klauer and van Hoof 2012).…”
Section: Introductionmentioning
confidence: 99%